ANALISIS PATTERN MAKING KEBAYA SISTEM CHUNG HWA UNTUK TUBUH BAGIAN ATAS BESAR - Rosita Carolina; Mei Indah Jayanti (Universitas Negeri Medan, 2015)
ABSTRACT Women with big upper body often have complaints on the clothing that is visible to be wrinkling, pull, fold and discomfort when wearing kebaya, because the woman who has big top there is fat which is on the chest, arms, and shoulders wider than the bottom. It is necessary to overcome the election pattern of what is appropriate for the woman in the big top, because not all pattern-making techniques can be used to create suit kebaya model for woman in the big top. The pattern making techniques that is used in this study is Chung Hwa pattern making system. This study aims to determine the results of kebaya stitching pattern making systems using the Chung Hwa in women with larger upper body. The method used was descriptive method. The subjects were 5 kebaya that use pattern (pattern) Chung Hwa with a round neckline and made of brocade. The data collection tool that was used was a sheet of observation and the observers in this study were 5 people consisting of some experts and practitioners in fashion. The results were analyzed using elementary statistical techniques (basic statistics) were depicted in the form of a percentage. On average the results of five observers then categorized very well with a score of 4, both with a score of 3, simply by a score of 2 and less with a score of 1. Results of the study revealed that of 11 indicators measured are nine indicators that obtain excellent category (81.82%) and 2 indicators gained good category (18.2%). Indicators that obtain excellent category is an indicator on the body circumference (100%), the indicator front of the neck (60%), the indicator back of the neck (60%), waist circumference indicator (100%), the indicator arm (60%), indicators the location of the shoulder line (60%), chest circumference below the indicator (80%), the length indicator (100%) and pelvic ring indicator (60%). Then two indicators that receive either category, namely indicators concave arm (100%) and the back layout indicator (100%). It can be concluded that the results kebaya stitching pattern making systems using the Chung Hwa at the top of the large-bodied women very well. Kata Kunci : Pattern making kebaya dan wanita tubuh besar